THE EFFECT OF MICROMANAGE LEADERSHIP STYLE ON GENERATION Z WORKERS: SELF-EFFICACY AS A MEDIATION OF JOB SATISFACTION - Sinaga, Boy Andika (PT. Jurnal Center Indonesia Publisher, 2025)
In order to show how a micromanaged leadership style impacts job satisfaction among generation Z employees, this study used self-efficacy as a mediating variable. The study's sample and demographic were Riau Province's Generation Z workers, who were born between 1997 and 2012. The sample size consisted of 203 respondents using a non-probability sampling approach and a questionnaire survey for data collection. The study's conclusions were tested using SmartPLS 3. It featured an outside model, like a validity and reliability test, and an interior model, such a model fit test and a research hypothesis test. The results of the investigation demonstrated the validity and accuracy of each indicator. The hypothesis test results demonstrated that job satisfaction was positively and significantly impacted by self-efficacy, that self-efficacy was positively and significantly impacted by micromanaged leadership style, and that job satisfaction was not significantly impacted by leadership style. Indirect hypothesis testing using self-efficacy as a mediator between job satisfaction and the micromanaged leadership style produced positive and significant results. The results of the study indicate that the relationship between work happiness and micromanagement leadership style can be totally mediated by self-efficacy.